Patterns of Extra-Abdominal Injuries and Mortality Risk Factors in Penetrating Abdominal Trauma: A Cross-Sectional Study - Waleed Abdulridha Oleiwi Al –Rikaby; Hasan Abd Hurab Alduraiby; Adnan Mohammed; Kamel Jwad Tahan Alfowa (American Journal of Biomedicine and Pharmacy, 2025)
Background: Penetrating abdominal trauma is a significant contributor to morbidity and mortality. Identifying associated extra-abdominal injuries and mortality risk factors is crucial for optimizing trauma care. Objective: To analyze the frequency of associated extra-abdominal injuries and assess mortality risk based on the mechanism of injury in patients with penetrating abdominal trauma. Methods: A cross-sectional study was conducted on 100 patients with penetrating abdominal injuries. Data on extra-abdominal injuries and mortality outcomes were collected and analyzed. Results: Extra-abdominal injuries were observed in 27% of cases. Chest injuries were the most common (18%), while head and neck injuries were the least frequent (1%). Mortality was significantly associated with the mechanism of injury. Gunshot wounds had the highest mortality rate (13%, p = 0.023), followed by shrapnel (6%), and knife injuries (5%). Conclusion: Chest injuries are the most frequent extra-abdominal injuries associated with penetrating abdominal trauma. Gunshot wounds represent a significant mortality risk and warrant focused clinical attention. Early identification of injury type and location is critical in improving trauma outcomes.